Evolutions and Managements of Soil Microbial Community Structure Drove by Continuous Cropping - Chen, Yudong; Du, Jianfeng; Li, Yang; Tang, Heng; Yin, Ziyi; Yang, Long; Ding, Xinhua (Frontiers in Microbiology, 2022)
Continuous cropping obstacles have increasingly become an important phenomenon affecting crop yield and quality. Its harm includes the deterioration of soil basic physical and chemical properties, changes of soil microbial community structure, accumulation of autotoxins, weakness of plant growth and aggravation of diseases and pests. In this review, the evolutionary trend of soil microbial structure driven by continuous cropping was generalized, while drivers of these changes summed up as destruction of soil microbial living environment and competition within the community. We introduced a microorganism proliferation and working model with three basics and a vector, and four corresponding effective measures to reshape the structure were comprehensively expounded. According to the model, we also put forward three optimization strategies of the existing measures. In which, synthetic microbiology provides a new solution for improving soil community structure. Meanwhile, to ensure the survival and reproduction of soil microorganisms, it is necessary to consider their living space and carbon sources in soil fully. This review provided a comprehensive perspective for understanding the evolutionary trend of the soil microbial community under continuous cropping conditions and a summary of reshaping measures and their optimization direction.